Risk factors for graft rupture after anterior cruciate ligament reconstruction: a systematic review with meta-analysis - Cronström, A.; Tengman, E.; Häger, C. K. (British Journal of Sports Medicine, 2021)
Background Underlying factors contributing to increased risk of graft rupture after anterior cruciate ligament reconstruction (ACLR) are not well described.